Kepuasan Self Monitoring Blood Glucose dengan Kualitas Hidup pada Pasien Diabetes Tipe 2 - Shanty Chloranyta; Yulia Yulia; Masfuri Sodikin (Poltekkes Kemenkes Bengkulu, 2019)
Self monitoring blood glucose (SMBG) is an integral part of diabetes self management. SMBG is effective in improving the quality of life there is a 40.6% increase in physical and emotional functioning of patients, and 39.13% confidence. SMBG is not effective in improving the quality of life of patients experiencing frustration, depression and suffering. The purpose of this study was to analyze SMBG satisfaction with quality of life. Cross sectional research design. The population of this study were 51 type 2 diabetes patients with purposive sampling technique. The instruments used were Glucose Monitoring Satisfaction Survey (GMSS), Diabetes Quality of Life Brief (DQoL Brief), Diabetes Self Management Questionnaire (DSMQ). Data analysis used Pearson test. The results showed respondents (78.4%) were female, (58.8%) had hypertension complications, (84.3%) financial support using BPJS, (62.7%) using insulin binding 32. The average age of 50.73 years, SMBG satisfaction 49.43, quality of life 49.84 , diabetes self management 28. There was a significant relationship between SMBG satisfaction and quality of life (p = 0.000). Satisfaction of SMBG improves quality of life in patients with type 2 diabetes.